1973 ネン カキ ナンキョク カイ インド ヨウク ノ トウケイ 13゜ セン ニ ソッテ エラレタ カイアシ ルイ シリョウ - 山田, 智; ヤマダ, サトシ; 谷村, 篤; タニムラ, アツシ; 箕田, 嵩; ミノダ, タカシ; Yamada, Satoshi; Tanimura, Atsushi; Minoda, Takashi (1991)
P(論文) 1973年2月27日から3月3日の間, 南極海インド洋区の東経13°線に沿った南緯51°以南の8観測点において採集したカイアシ類の種組成を調査した。採集は, ノルパックネット(口径45cm, 目合0.33mm)を用いて水深200mから表面までの鉛直曳によって行われた。各測点ともカイアシ類が最も卓越して出現し, 動物プランクトン総個体数の80%以上を占めた。Oncaeidaeを除く13属15種類のカイアシ類が同定され, Calanus propinquus, Calanoides acutus, Ctenocalanus vanusおよびOithona similisは優占して出現した。C. propinquus, C. acutusおよびC. vanusは南緯60°から63°付近で卓越して出現した。また, O. similisは南緯56°および62°付近で多く出現した。その他, Calanus simillimus, Rhincalanus gigas, Clausocalanus laticeps, Euchirella rostromagna, Euchaeta antarctica, Racovitzanus antarcticus, Scolecithricella glacialis, Metridia lucens, Metridia gerlachei, Heterorhabdus austrinusおよびHaloptilus oxycephalusの11種の出現個体数はわずかであった。 Zooplankton samplings were conducted at 8 stations in the Indian sector of the Antarctic Ocean along 13°E from 27 February to 3 March in 1973 by the 14th Japanese Antarctic Research Expedition. Vertical hauls from 200m to the surface with a Norpac net (45cm in diameter, 0.33mm mesh openings) were carried out. Copepoda occupied more than 80% of the total individual numbers of zooplankton at all stations. The species composition and abundance of copepods were investigated. A total of 15 species except for Oncaeidae were recorded. Calanus propinquus, Calanoides acutus, Ctenocalanus vanus and Oithona similis were numerically important components. Especially C. propinquus, C. acutus and C. vanus occurred abundantly at three stations between 60°S and 63°S and O. similis was abundant near 56°S and 62°S. Other eleven species, Calanus simillimus, Rhincalanus gigas, Clausocalanus laticeps, Euchirella rostromagna, Euchaeta antarctica, Racovitzanus antarcticus, Scolecithricella glacialis, Metridia lucens, Metridia gerlachei, Heterorhabdus austrinus and Haloptilus oxycephalus were small in numbers. departmental bulletin paper